"Easterlies"‐induced precipitation in eastern Patagonia: Seasonal influences of ENSO'S FLAVOURS and SAM. (26th February 2020) - Agosta, Eduardo A.; Hurtado, Santiago I.; Martin, Paula B.
Abstract: The seasonal influence of the phases of El Niño‐Southern Oscillation (ENSO) and of Southern Annular Mode (SAM) on precipitation over eastern Patagonia is examined. Also, their impact in generating persistent daily easterly moisture flux leading to daily precipitation events. The significant signatures of the drivers on precipitation are found in March–April–May (MAM), June–July–August (JJA) for ENSO and November–December–January (NDJ) for SAM. Over the east coast, precipitation is mainly favoured owing to an overall growth of the seasonal mean number of precipitation days (~30%) by central Niño in JJA and by negative SAM phase in NDJ, and growth of the frequency of persistent events of daily westward moisture flux (~90%) by eastern Niña in MAM. A great spatial variability shapes the anomalies. Evidence is shown for weakened seasonal westerlies linked to Eastern Pacific Niño in MAM. Enhanced daily easterlies with net daily westward moisture flux in the region lead to strong daily precipitation. Growth in precipitation intensity in the northeast coast is also associated with Eastern Pacific Niño in MAM. In the interior lands, south of 45°S, westward moisture flux is increased up to ~200% by negative SAM phase in NDJ. The nature of extratropical low‐frequency transient eddies travelling over the South Pacific will influence the frequency and intensity of daily local precipitation as well as the persistent westward flux during ENSO events. Abstract : Schematic of daily circulation anomalies at 300 hPa and surface, linked to daily coastal precipitation features in central‐eastern Patagonia under central Niña (moC−), central Niño (moC+) and eastern Niño (moE+) in MAM and JJA. H (L) stands for anticyclonic (cyclonic) eddy anomaly; PP, precipitation; MF, moisture flux (horizontal arrow). Chart insert qualitatively shows the changes in the number (#) of PP days, daily PP days, and # of days with persistent "easterlies". Upward (downward) arrow stands for increase (decrease).